Tanggung Jawab Penyiaran Berita di Radio 107,5 PRFM - Azizah, Sheeny Nurul Rahma; Anugrah, Dadan; Muhaemin, Enjang (Annaba: Jurnal Ilmu Jurnalistik, 2020)
The purpose of this study was to determine the form of responsibility carried out by 107.5 PR FM in broadcasting a news to the public according to the language of radio journalism. Then the form of news validation which before being broadcast used radio journalistic language by 107.5 PR FM and the application of radio journalistic language that has been carried out by 107.5 PR FM. The data collection techniques in this study were observation, interviews, and document review. By using qualitative descriptive methods and research samples totaling 5 informants have been obtained using purposive techniques. The result of this research is to give a form of responsibility as radio media to listeners, by broadcasting news that is not hoax and always using radio journalistic language in broadcasting.